Exploring the Relationship between Rework Projects and Risk Indicators. Issue 4 (August 2015) - Yim, Rachel L.; Castaneda, Jason M.; Doolen, Toni L.; Tumer, Irem Y.; Malak, Richard
When projects fail to adequately meet requirements, organizations are forced to either abandon the project or to initiate a new project to address the original project requirements. Because the organization already has experience with and exposure to many project details, it is possible that the second attempt to address the original requirements (a rework project) will create different challenges for the project team. The purpose of this study was to examine risk indicators for rework projects and to determine whether or not risk indicators were the same or different for rework projects. A risk indicator is a factor that has predictive power about the likelihood of a risk occurring in the course of a project's life cycle. The projects studied for this research were undertaken by a large engineering design organization. The results show that there are some important differences in the types of risk indicators experienced by project managers and project teams in rework projects. Specifically, the risks associated with project urgency, quality, and technological changes were more common in rework projects. By understanding and attending to these differences in rework project risks, project managers will be better equipped to successfully guide rework projects to completion.